Citizen trust in health institutions - محمد, الأستاذ المساعد د. كردستان عمر محمد; فرج, م.م. چرۆ محمد (Sulaimani Journal for Humanities, 2025)
To determine citizens' trust in health institutions, by presenting scientific interpretations about the principles, dimensions, types, and methods of trust in health institutions. This paper provides a scientific analytical description, drawing on scientific literature and previous scientific research on the role of trust in public health, based on the scientific basis of motivation theory, specifically rational choice theory, and trust theories and models. Citizen trust in health institutions is a need-motivated behavior that is organically and naturally formed as a result of biological, psychological, and social interactions that direct and control behavior, it is based on faith and the leap of faith. It is formed and emerges from infancy and manifests itself in every situation of daily life. It is formed, grows or destroys cyclically through positive interaction and can be rebuilt. Citizens' trust in health institutions is related to the expected positive exchange between them and is two-sided and one-way, partly related to the motivation of citizens' needs that encourage, the other part of health institutions that cause trust in society. Two parts of citizen trust in health institutions are one-way. Citizen trust in health institutions is different from trust or trust in health institutions because individuals and health institutions have similar motivations for trust, but they are different in trusting behavior (Their trust point are different) and they are complemental or matching.
Keywords: Trust; public health; theoretical foundation of trust; dimension of trust; type of trust; style of trust